Tax Non-Compliance Risks of Licensed Importers in Indent-Based Import - Suyani, Emik (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines administrative data about indent-based imports by licensed importers and its implications for tax compliance and possible tax revenue loss. Employing a descriptive-analytical methodology, it amalgamates tax return and import payment data to evaluate compliance risks among corporate taxpayers. The study incorporates 268 licensed importers registered in West Jakarta for the 2024 tax year. The analysis reveals that 79% of the observed taxpayers are categorized as having the highest level ofrisk. These taxpayers collectively claimed around IDR 20 billion in Article 22 Income Tax and VAT credits on imports. Supervisory evaluations revealed discrepancies amounting to IDR 5.46 billion, of which IDR 5.03 billion was recovered from the highest-risk category. These findings show proxy-based indications of compliance risk. The results underscore the necessity to fortify beneficial ownership alignment and improve the integration of tax and customs data via risk-based validation of import-related tax credits.